Comparison of endovenous laser ablation and conservative treatment in acute thrombophlebitis of the varicose great saphenous vein: rationale, design and first results of clinical trial - K. A. Kaperiz; A. O. Rastatueva; I. S. Yavelov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Thrombophlebitis of the superficial lower limb veins is one of the most common complications of chronic vein disease. Nowadays a long-term (at least 45 days) subcutaneous injection of fondaparinux sodium or heparin in combination with elastic compression of the limb is recommended for treatment of superficial vein thrombosis with a moderate risk of thrombus propagation to deep venous system. However, long-term use of anticoagulants is not always possible and sometimes contraindicated. Endovenous laser ablation (EVLA) around thrombus-free junction of great or small saphenous veins without subsequent long-term use of anticoagulants seems to be a promising intervention for treatment of acute thrombophlebitis of varicose superficial veins.The prospective single-center randomized open-label clinical trial was dedicated for comparison the efficacy and safety of three following treatments options for patients with acute thrombosis of the varicose great saphenous vein and location of thrombi in the trunk and/ or its large inflows: EVLA close to saphenous vein junction without anticoagulation, EVLA and 7 days of anticoagulation and noninvasive treatment with anticoagulation for 45 days (subcutaneous injections of the fondaparinux 2,5 mg). Class 2 compression stockings are used in all patients. Adverse outcomes are recorded at 7, 45 and 90 days after randomization. These include the progression of superficial vein thrombosis, recurrent superficial vein thrombosis, thrombosis involvement of the superficial segment of the perforating vein up to the fascia, deep vein thrombosis according to compression ultrasound, and pulmonary embolism with symptoms. Bleedings according to the World Society of Thrombosis and Hemostasis and the Academic Research Consortium classification as well other complications are also recorded. The first 30 patients included in the study have a low incidence of venous thrombosis risk factors and localization of the thrombus relatively far from the saphenofemoral junction. EVLA resulted in persistent cessation of venous blood flow at the intervention site. New episodes of venous thrombosis were noted only in the group of medical treatment — deep vein thrombosis of the contralateral tibia 5 days after stopping of 45-day treatment with fondaparinux and thrombus in the recanalized inflow of the great saphenous vein without involving its trunk at the 21st day after stopping of 45-day injection of fondaparinux. There were no complications in the area of intervention and bleedings.